FORMULASI NASI INDIGENOUS (BERAS CISOKAN) DENGAN MAKANAN KHAS SUMATERA BARAT SEBAGAI PRODUK PANGAN DARURAT - Refdi, Cesar Welya; Fajri, Prima Yaumil; Rasdiana, Felga Zulfia (JURUSAN ILMU DAN TEKNOLOGI PANGAN, UNIVERSITAS HALU OLEO, 2021)
The critical part of disaster mitigation is getting the food needs of disaster victims, namely emergency food. Emergency Food Products (EFP) are processed food products specifically designed to meet humans' daily energy needs (2100 kcal) and are consumed in abnormal situations. West Sumatra has a variety of traditional cuisine that is liked by various people especially in Indonesian peoples. This study aimed to determine the formulation of indigenous rice (Cisokan Rice) and traditional West Sumatra dishes as emergency food based on nutritional composition to meet IOM emergency food standards. This research obtained three formulations of Emergency Food products using traditional foods from West Sumatra. These formulations, namely Rice with Rendang, Rice with Chicken Kalio, and Rice with Fish Asam padeh. Each formulation consists of 250 grams per serving. Each product formulation also meets the requirements for emergency food consumption, namely 2100 kcal per day, which can be fulfilled with 3-4 portions of consumption a day.